Reaction assessment of cultured breast cancer cells exposed to anticancer agents using microscale acoustic impedance profile. (26th June 2018) - Rahayu, Rahma Hutami; Takanashi, Kyoichi; Soon, Thomas Tiong Kwong; Seviaryna, Inna; Maev, Roman; Kobayashi, Kazuto; Hozumi, Naohiro; Yoshida, Sachiko
Abstract: The mechanical properties of living cells are known to be associated with disease states and cell function. In this study, acoustic impedance microscopy using a sapphire lens transducer with a center frequency of 320 MHz was employed to characterize the elasticity of the C127I cell line against an anticancer drug, nimustine hydrochloride (ACNU), and an anticancer agent, betulinic acid (BA). Confocal laser scanning microscopy was also used to investigate the drug affecting actin filaments, the nucleus, and mitochondria structures. Breast cancer cells were found to have significantly lower acoustic impedance after treatment with ACNU and BA than intact cells. Confocal images showed a significant difference in the localization of actin filaments and mitochondria structures, which suggested a difference in cell elasticity. An important insight emerging from this work is that the acoustic impedance of cells may potentially serve as a useful biomarker for anticancer drug efficacy tests, as diseases such as cancer have their own particular mechanical properties.